The new politics of Islam : pan-Islamic foreign policy in a world of states - Sheikh, Naveed S., 1975- (RoutledgeCurzon, 2003)
This text examines how Islam is to be understood in relation to contemporary international relations. It highlights salient characteristics in pan-Islamic theory and its implications.